h=32+14t-1+-16t

Simple and best practice solution for h=32+14t-1+-16t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h=32+14t-1+-16t equation:


Simplifying
h = 32 + 14t + -1 + -16t

Reorder the terms:
h = 32 + -1 + 14t + -16t

Combine like terms: 32 + -1 = 31
h = 31 + 14t + -16t

Combine like terms: 14t + -16t = -2t
h = 31 + -2t

Solving
h = 31 + -2t

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Simplifying
h = 31 + -2t

See similar equations:

| -(6x+3)-(-5x-8)=3 | | (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 | | ln(x)+ln(x+4)=0 | | 15y-3=29-y |

Equations solver categories